A Novel Approach to Latent Class Modelling: Identifying the Various Types of Body Mass Index Individuals. (25th February 2020) - Brown, Sarah; Greene, William; Harris, Mark
Summary: Given the increasing prevalence of adult obesity, furthering understanding of the determinants of measures such as the body mass index ( BMI ) remains high on the policy agenda. We contribute to existing literature on modelling the BMI by proposing an extension to latent class modelling, which serves to unveil a more detailed picture of the determinants of BMI. Interest here lies in latent class analysis with a regression model and predictor variables explaining class membership, a regression model and predictor variables explaining the outcome variable within BMI classes and instances where the BMI classes are naturally ordered and labelled by expected values within class. A simple and generic way of parameterizing both the class probabilities and the statistical representation of behaviours within each class is proposed, that simultaneously preserves the ranking according to class-specific expected values and yields a parsimonious representation of the class probabilities. Based on a wide range of metrics, the newly proposed approach is found to dominate the prevailing approach and, moreover, results are often quite different across the two.